Rules and discretion(s) in prudential regulation and supervision: Evidence from EU banks in the run-up to the crisis - Angela Maddaloni; Alessandro Scopelliti (European Central Bank (ECB), 2019)
Prior to the financial crisis, prudential regulation in the EU was implemented non-uniformly across countries, as options and discretions allowed national authorities to apply a more favorable regulatory treatment. We exploit the national implementation of the CRD and derive a country measure of regulatory flexibility (for all banks in a country) and of supervisory discretion (on a case-by-case basis). Overall, we find that banks established in countries with a less stringent prudential framework were more likely to require public support during the crisis. We instrument some characteristics of bank balance sheets with these prudential indicators to investigate how they affect bank resilience. The share of non-interest income explained by the prudential environment is always associated with an increase in the likelihood of financial distress during the crisis. Prudential frameworks also explain banks' liquidity buffers even in absence of a specific liquidity regulation, which points to possible spillovers across regulatory instruments.
Keywords: G01; G21; G28; 330; Prudential Regulation and Supervision; European Banking; Cross-country Heterogeneities; Rules versus Discretion; Banking Union